Urban Farming Center dengan Pendekatan Arsitektur Berkelanjutan di Kota Makassar - Najib, Muhammad Ainun; Marwati, Marwati; Nursyam, Nursyam (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2025)
Urban farming is a type of agriculture practised by city dwellers to produce organic, healthy food free from chemicals, aiming to improve life quality through healthy food consumption. However, urban residents often choose unhealthy lifestyles and consume fewer vegetables. The most common barriers are categorised as technical and non-technical. This study investigates how sustainable architectural concepts can be applied both passively and actively in the design of the Urban Farming Centre in Makassar. Data was collected through field observations, interviews, and literature research, then analysed using synthesis methods to develop an appropriate design concept. The study indicates that urban farming centres can use sustainable passive and active designs to enhance energy efficiency, thermal comfort, and ecological sustainability. Passive designs, such as building orientation and natural shading, save energy, while active designs, such as solar panels and agricultural technologies, support energy sustainability and food security. According to this research, the Urban Farming Centre can function as a food production facility and as an educational hub, teaching farmer groups and the community to enhance food security in line with the region's potential.